Plant Species Composition and Their Conspecific Association in Natural Tropical Rainforest, South Papua - Agustinus Murdjoko; Djoko Marsono; Ronggo Sadono; Suwarno Hadisusanto (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Papua has so many wide lowland areas that cover high diversity in plant from life-forms. In contrast, there is a lack of information concerning species diversity. The objectives of the research were to describe species of plant life-forms and described conspecific associations between small individuals and large individuals in natural tropical rainforest, south Papua. Then, 46 nested plots were placed systematically in natural tropical rainforest of Boven Digoel Regency, Papua. Density, frequency, dominance and importance value index (IVI) were analyzed to describe plant diversity, while detrended correspondence analysis (DCA) was to describe conspecific association between small individuals and large individuals. Results found 2040 individuals in this forest consisting 194 plant species. Those are from pteridophytes, angiosperms and gymnosperms. The plant life-forms are herbs, orchids, palms, pandans, shrubs, rattans, vines and trees in which of the plant life-forms, trees are the most abundant according to number of species. In the dominant plant species, two types of conspecific association occurred between small individuals and large individuals. Analysis of DCA revealed that three are large plant species grow along with their small individuals. Another type is that small individuals grow far from their large individuals.